Long non-coding RNA FENDRR reduces prostate cancer malignancy by competitively binding miR-18a-5p with RUNX1. (4th July 2018) - Zhang, Guanying; Han, Guangye; Zhang, Xinjun; Yu, Quanfeng; Li, Zeyu; Li, Zhenhui; Li, Jianchang
Abstract: Context: Prostate cancer (PCa) is one of the most commonly diagnosed malignancy in men in the western world. Objective: We aim to investigate the biological role of long non-coding RNA FENDRR and its mechanism in PCa. Materials and methods: We determined the expression of FENDRR and miR-18a-5p in PCa tissues and examined the regulatory mechanism in PCa cell lines. Results: FENDRR transcripts in human PCa tissues were significantly decreased compared with the normal controls. Reduced expression of FENDRR was correlated with the increase of pathological degree and poor prognosis in PCa patients. Upregulation of FENDRR inhibited cell proliferation, increased apoptosis and decreased invasion and migration ability, which was inhibited by miR-18a-5p mimic. Knockdown of FENDRR resulted in a significant increase of PCa cell proliferation and decrease of apoptosis and this effect was inhibited miR-18a-5p inhibitor. FENDRR and RUNX1 contain potential target sites for miR-18a-5p. miR-18a-5p mimic inhibited RUNX1 expression and luciferase activity. FENDRR could increase RUNX1 expression, which was inhibited by miR-18a-5p. The effect of FENDRR on cell proliferation, apoptosis and invasion and migration ability was suppressed by silence of RUNX1. Discussion and conclusion: These results position FENDRR/miR-18a-5p/RUNX1 as a potential therapeutic target and biomarker for PCa.